Serologic Evidence For Circulating Orthopoxviruses In Peridomestic Rodents From Rural Uganda - Salzer, Johanna S.; Carroll, Darin S.; Rwego, Innocent B.; Li, Yu; Falendysz, Elizabeth A.; Shisler, Joanna L.; Karem, Kevin L.; Damon, Inger K.; Gillespie, Thomas R. (Journal of wildlife diseases, 2013)
The prevalence of orthopoxviruses (OPXV) among wildlife, including monkeypox virus (MPXV), remains largely unknown. Outbreaks of human monkeypox in central Africa have been associated with hunting, butchering, and consuming infected forest animals, primarily rodents and primates. Monkeypox cases have not been reported in east Africa, where human contact with wildlife is more limited. Whether this lack of human disease is due to the absence of MPXV in rodents is unknown. However, testing of wildlife beyond the known geographic distribution of human cases of monkeypox has rarely been conducted, limiting our knowledge of the natural distribution of MPXV and other OPXV. To improve our understanding of the natural distribution of OPXV in Africa and related risks to public health, we conducted a serosurvey of peridomestic rodents (Rattus rattus) in and around traditional dwellings in Kabarole District, Uganda, from May 2008 to July 2008. We tested for OPXV antibody in areas free of human monkeypox. Sera from 41%of the R. rattus individuals sampled reacted to OPXV-specific proteins from multiple, purified OPXV samples, but did not react by enzyme-linked immunosorbent assay. The specific OPXV could not be identified because poxvirus DNA was undetectable in corresponding tissues. We conclude that an OPXV or a similar poxvirus is circulating among wild rodents in Uganda. With the known geographic range of OPXV in rodents now increased, factors that dictate OPXV prevalence and disease will be identified.
Keywords: ELISA, monkeypox, Orthopoxvirus, poxvirus, Rattus, rodent, Uganda, Western blot.